Analysis of Arabic Textbooks Grade X Scientific Approach Curriculum 2013 Perspectives Rusydi Ahmad Thu'aimah - Sintya Rahmadewi; Muhaiban (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This article discusses the analysis of grade X Arabic language books based on the 2013 Curriculum's scientific approach. The main purpose of this research is to find out the extent to which the book implements the five steps of the scientific approach, namely observing, questioning, trying, reasoning, and communicating. This research uses descriptive qualitative method with content analysis technique as the research technique, focusing on Rusydi Ahmad Thu'aimah's theory as a guideline in data processing and presentation. Data were obtained through documentation study of textbooks used in senior high schools (SMA) and madrasah aliyah (MA). The results of the analysis show that the book has accommodated most of the elements of the scientific approach, especially in the activities of observing and trying. However, the aspects of questioning and communicating still need strengthening to make the learning process more active and meaningful. These findings are expected to be input for book writers and curriculum developers in improving the quality of Arabic teaching materials in accordance with the characteristics of the 2013 Curriculum.